Analisis Kemampuan Gaya Kepemimpinan Dan Lingkungan Kerja Dalam Mempengaruhi Motivasi Dengan Memperhatikan Mediasi Kepuasan Kerja: (Studi Karyawan Koperasi Syariah Alfa Mabruk Di Kabupaten Pasuruan) - Roziki, Fahri; Muryati, Muryati; Mas, Nasharuddin (Maisyatuna, 2024)
The aim of this research is to obtain empirical evidence regarding the ability of leadership style and work environment to motivate, both directly and through the mediation of job satisfaction. This type of research is quantitative with the SEM-SmartPLS method. Data was obtained through a questionnaire distributed to 35 census employees of the Alfa Mabruk Syariah Cooperative in Pasuruan Regency. Empirical evidence shows that directly, neither leadership style nor the work environment are able to encourage increased motivation. However, through the mediation of job satisfaction, these two independent variables are able to encourage increased motivation. This indicates the strong mediating role of job satisfaction, which also directly influences the motivation of employees of the Alfa Mabruk Syariah Cooperative in Pasuruan Regency.